1997
DOI: 10.1046/j.1471-4159.1997.69041508.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dietary Excitotoxins β‐N‐Methylamino‐l‐Alanine and β‐N‐Oxalylamino‐l‐Alanine Induce Necrotic‐ and Apoptotic‐Like Death of Rat Cerebellar Granule Cells

Abstract: Abstract:The neurotoxic properties of the dietary excitotoxins /3-N-methylamino-L-alanine and~3-N-oxalylamino-L-alanine have been studied in rat cerebellar granule cells and compared with those of glutamate. Glutamate caused dose-dependent death of cerebellar granule cells after a 30-min exposure when viability was assessed 24 h later. ß-N-Methylamino-L-alanine and /3-N-oxalylamino-L-alanine, however, were toxic only after 24 or 48 h of exposure. The neurotoxic effects of ß-N-methylaminO-L-alanine were blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…This creates an endogenous reservoir of neurotoxin within the human body, capable of slow release into cerebral and other tissues during protein catabolism for years or decades after its consumption. In vivo (Spencer et al, 1987;Smith and Meldrum, 1990;Rakonczay et al, 1991;Chang et al, 1993;Santucci et al, 2009) and in vitro studies have reported that BMAA acts as a glutamate agonist onto spinal motoneurons (Rao et al, 2006) and cortical (Lobner et al, 2007) and cerebellar (Staton and Bristow, 1997) neurons. However, a detailed description of its actions on substantia nigra pars compacta (SNpc) dopaminergic cells (DAergic) is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This creates an endogenous reservoir of neurotoxin within the human body, capable of slow release into cerebral and other tissues during protein catabolism for years or decades after its consumption. In vivo (Spencer et al, 1987;Smith and Meldrum, 1990;Rakonczay et al, 1991;Chang et al, 1993;Santucci et al, 2009) and in vitro studies have reported that BMAA acts as a glutamate agonist onto spinal motoneurons (Rao et al, 2006) and cortical (Lobner et al, 2007) and cerebellar (Staton and Bristow, 1997) neurons. However, a detailed description of its actions on substantia nigra pars compacta (SNpc) dopaminergic cells (DAergic) is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…3 mM BMAA- (Staton and Bristow, 1997) and 3 mM ACPD-induced death (results not shown) were not significantly greater than controls until 12 h of exposure.…”
Section: Measurement Of Glutamate- Bmaa- and Acpdinduced Cgc Deathmentioning
confidence: 73%
“…1993b; Toms et al, 1995). The CGCs used in our experiments were age 12-14 D1V, because this was optimal for studying glutamate-and BMAA.-induced CGC death (Staton and Bristow, 1997). To determine whether the lack of an mGluR-induced Ca 2~rise in CGCs age 12-14 DIV was due to limited expression of group I mGluRs, short ACPD and DHPG exposure experiments were also pei-formed in CGCs age 4 DIV.…”
mentioning
confidence: 99%
“…Both hypofunction and overstimulation of NMDAR can cause cell death. Blockade of NMDAR elicits apoptosis, while overstimulation of NMDAR can trigger either apoptosis or necrosis, depending on the intensity of receptor activation (Bonfoco et al, 1995; Staton and Bristow, 1997). Precisely, short exposure to low concentrations of glutamate or NMDA evokes apoptosis in cortical neurons (Leist et al, 1999), whereas intense exposure to high concentrations of NMDA or glutamate induces necrotic cell damage (Bano et al, 2005).…”
Section: Introductionmentioning
confidence: 99%